PELAKSANAAN MEDIASI DALAM PERMA NOMOR 1 TAHUN 2016 DAN PERMA NOMOR 3 TAHUN 2022 (Suatu Perbandingan) - Maria Rosalina (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
Before examining, adjudicating and deciding on the main case, the panel of judges first orders the parties to mediate. Advances in science, technology and communication also have an impact on the implementation of manual mediation, as stipulated in Perma No.1 of 2016. As a result, Perma No.1 of 2016 is refined with Perma No.3 of 2022 where mediation can be carried out directly or electronically, based on the agreement of the parties. Of course there are differences and similarities in the implementation of mediation regulated in No.1 of 2016 and Perma No.3 of 2022. Keywords: Mediation, Perma, A Comparison